2023
DOI: 10.1177/15210251231198006
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Thematic Analysis of First-Generation College Students’ Help-Seeking Attitudes, Decisions, and Behaviors

Matthew Hagler,
Renesha Johnson,
Johnathan Boags
et al.

Abstract: First-generation college students (FGCS) are significantly less likely to complete degrees compared to continuing-generation students. Among the multifaceted causes for this disparity, many FGCS possess limited social and cultural capital in academia, resulting in lower rates of help-seeking and resource utilization. In this study, we conducted an in-depth qualitative investigation to better understand FGCS's help-seeking attitudes, decisions, and behaviors. Twenty-five first-year FGCS at a 4-year, regional, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Social support, including parental validation, is particularly important, and has been associated with positive student experiences (Roksa et al, 2021). While FIF students value self-efficacy, they have been reported as seeking help if potential empathetic and non-judgmental support is accessible (Hagler et al, 2023). Having a sense of belonging is also of relevance, as studies have reported a lower sense of belonging perceived by FIF students (Kreniske et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Social support, including parental validation, is particularly important, and has been associated with positive student experiences (Roksa et al, 2021). While FIF students value self-efficacy, they have been reported as seeking help if potential empathetic and non-judgmental support is accessible (Hagler et al, 2023). Having a sense of belonging is also of relevance, as studies have reported a lower sense of belonging perceived by FIF students (Kreniske et al, 2022).…”
Section: Introductionmentioning
confidence: 99%